A Re‐examination of the Impact of the UK National Minimum Wage on Employment. (26th July 2015) - Dickens, Richard; Riley, Rebecca; Wilkinson, David
<x xml:space="preserve">Abstract</x> Early work on the national minimum wage (NMW) suggested that policymakers in the UK had succeeded in raising the pay of low‐paid workers without impairing their employment prospects. This paper shows that when we focus on the most vulnerable workers, part‐time females, the NMW appears to be associated with reductions in employment retention. These negative impacts were evident when the NMW was introduced and also when it was increased faster than average wages in the mid‐2000s. We also show that these falls in employment among part‐time females are exacerbated by the recession.